Stability Studies of Transition Metal Chelates of 5-Bromosalicylidene-4-methoxyaniline andSalicylidene-2,3-dimethylaniline as Ligands - N. G. Nadkarni; K. V. Mangaonkar (E-Journal of Chemistry)
Binary and ternary complexes of the type M-Y and M-X-Y [M = Mn(II), Ni(II), Cu(II) and Zn(II); X = 5-bromosalicylidene-4-methoxyaniline and Y = salicylidene-2,3-dimethylaniline] have been examined pH-metrically at 27±0.5 °C and at constant ionic strength, μ = 0.1 M (KCl) in 75 : 25(v/v) 1,4-dioxne-water medium. The stability constants for binary (M-Y) and ternary (M-X-Y) systems were calculated.